2018
DOI: 10.1021/acs.langmuir.8b03056
|View full text |Cite|
|
Sign up to set email alerts
|

Adsorption and Interfacial Layer Structure of Unmodified Nanocrystalline Cellulose at Air/Water Interfaces

Abstract: Nanocrystalline cellulose (NCC) is a promising biological nanoparticle for the stabilization of fluid interfaces. However, the adsorption and interfacial layer structure of NCC are poorly understood as it is currently unknown how to form NCC interfacial layers. Herein, we present parameters for the adsorption of unmodified NCC at the air−water (A/W) interface. Initial NCC adsorption is limited by diffusion, followed by monolayer saturation and decrease in surface tension at the time scale of hours. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 68 publications
11
107
1
Order By: Relevance
“…Bertsch et al reported that for unmodified CNC, a diffusion limited time lag is observed before adsorption occurrs, 15 whilst, similarly to the results herein described, Scheuble et al showed that the kinetic of adsorption for methylated CNP is not delayed by a time lag. 21 This suggests that CNP hydrophobization or interfacial polyelectrolyte-CNP charge complexation (as herein described) are effective strategies to decrease the energy barrier for CNP adsorption at the W/O interface.…”
Section: Interfacial Shear Rheologysupporting
confidence: 76%
See 1 more Smart Citation
“…Bertsch et al reported that for unmodified CNC, a diffusion limited time lag is observed before adsorption occurrs, 15 whilst, similarly to the results herein described, Scheuble et al showed that the kinetic of adsorption for methylated CNP is not delayed by a time lag. 21 This suggests that CNP hydrophobization or interfacial polyelectrolyte-CNP charge complexation (as herein described) are effective strategies to decrease the energy barrier for CNP adsorption at the W/O interface.…”
Section: Interfacial Shear Rheologysupporting
confidence: 76%
“…Recently, Bertsch et al reported on the spontaneous adsorption of CNC at water/air (W/A) interface without the addition of any chemical modification or additional species (e.g., surfactants). 15 In this field, three main approaches have been broadly employed to tune the wettability of CNP, favouring their adsorption to the interface: (i) electrostatic complexation between oppositely charged CNP and water-soluble amphiphilic species (e.g., surfactants), [16][17][18] (ii) covalent hydrophobization of the CNP interface, [19][20][21] and, (iii) interfacial polyelectrolyte-CNP charge complexation between a polyelectrolyte, which is largely soluble in the organic phase (e.g., oil), and an oppositely charged water-dispersible CNP. This last approach relies on the use of two immiscible liquids as scaffolds, delivering two oppositely-charged species and directing assembly across the liquid-liquid interface, analogously to the more extensively studied complex coacervates.…”
Section: Introductionmentioning
confidence: 99%
“…A bulk concentration of 0.5 wt% CNCs was chosen, which corresponds to the maximum CNC surface coverage at air-water (A/W) interfaces. 12 CNCs adsorbed at the n-alkane interfaces with measurable changes in normalized surface pressure p norm for 24 h. CNC adsorption was independent of n-alkane chain length and achieved a maximum p norm of 0.23 AE 0.01 (from asymptotic ts). These adsorption kinetics are in good agreement with previous ndings on CNC adsorption at the A/W interface.…”
Section: Resultsmentioning
confidence: 96%
“…The employed CNCs are 79 AE 6 nm long and 5 nm in height with a linear charge density of 0.67 nm À1 . 12,13 The detailed Experimental section is provided in the ESI. †…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation